PENDUGAAN PERAMALAN EARNING PER SHARE SAHAM LQ45 - Elva Susanti (Universitas Putera Batam, 2019)
This study aims to determine the best forecasting method and determine which companies have earnings per share share reports with the smallest MAD and MSE forecasting results. The forecasting method is Moving average, and exponential smooting with trend alpha 0.3 and betta 0.3 values using the QM POM program. The sample used was LQ45 shares from 2013 to 2017. The results of forecasting moving average values of MAD = 0.02 and MSE 0.014 and exponential forecasting smooting with trend values of MAD = 0.375 and MSE 0.248.